Implementing Weighted Product Method In Determining Qualified Lesung coffee - Hakim, Lukman (Adpebi Science Series, 2022)
One of the technological advances is the technology in information through the internet. The impact of advances in internet technology has now penetrated the business world and one of which is the coffee business. Lesung coffee is 100% original coffee without a mixture of chemicals, which is processed by pounding using traditional Lesung tools. This results in uniqueness inthe coffee and has a strong aroma. However, in determining the quality of Lesung Coffee, PT. Hafizh Lesung Blessings still uses the manual method, namely by touching the texture of the coffee and smelling the coffee aroma. This is not hygienic and the quality is not guaranteed. To overcome these problems, a system was built by applying the Weighted Product method. The Weighted Product method is considered appropriate to overcome the existing problems because it is able to select the best alternative from a number of alternatives and its advantages in weighting techniques. The results of this study were in the form of a web-based application of the application of the Weighted Product Method in Determining the quality of Lesung Coffee. The results of the weighted product ranking method were determined by the highest value as the final decision of the system.